Strategi Pengelolaan Wakaf Uang di Pondok Modern Tazakka - Wawan Tyas Setyawan; Khusniati Rofi'ah (Institut Agama Islam Negeri Ponorogo, 2023)
The understanding of waqf is not evenly distributed among the people, especially regardingwaqf and types of waqf, productive management of waqf land assets is not yet optimal, naziris not professional. Waqf management is closely related to Nadzir's ability to manage. Inorder to expedite the management of cash waqf which is still quite unfamiliar to thecommunity, it is necessary to increase both knowledge and management. The research in thispaper aims to determine the cash waqf management organization in Islamic Boarding SchoolTazakka, to find out cash waqf management products in Islamic Boarding School Tazakka andto find out the impact of cash waqf management on Islamic Boarding School Tazakka. Thisresearch is a type of field research using a qualitative approach. Data obtained with primaryand secondary data. The results of this study. First, there is the management of cash waqf atthe Tazakka Modern Islamic Boarding School, Batang City. The management model atPondok Modern Tazakka is generally the same as other institutions, namely the wakif handsover his assets to the nadzir to be managed and then the wakif receives a cash waqf certificate.The management is seen from six aspects, namely the use of cash waqf, cash waqfmanagement team, waqf instruments, cash waqf limits, Islamic financial institutions andcash waqf certificates. The two types of waqf that are applied in Islamic Boarding SchoolTazakka is easily accepted in society. The three have an impact on the development of Islamicboarding schools and community acceptance